2016
DOI: 10.1186/s12879-016-1906-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of first-line antimicrobial resistance in multi-drug and extensively drug resistant strains of Mycobacterium tuberculosis in KwaZulu-Natal, South Africa

Abstract: BackgroundIn South Africa, drug resistant tuberculosis is a major public health crisis in the face of the colossal HIV pandemic.MethodsIn an attempt to understand the distribution of drug resistance in our setting, we analysed the rpoB, katG, inhA, pncA and embB genes associated with resistance to key drugs used in the treatment of tuberculosis in clinical isolates of Mycobacterium tuberculosis in the KwaZulu-Natal province.ResultsClassical mutations were detected in the katG, inhA and embB genes associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… 31 , 45 , 47 51 This was followed by Mycobacterium tuberculosis accounting for 11.3% (n=6) of the reviewed articles. 33 , 34 , 37 , 41 , 42 , 46 Five reviewed articles (9.4%) studied E. coli 40 , 52 , 53 and Enterococcus spp. 30 , 54 56 Two different strains of E. coli were also studied, namely E. coli ST131 35 and O157:H7.…”
Section: Resultsmentioning
confidence: 99%
“… 31 , 45 , 47 51 This was followed by Mycobacterium tuberculosis accounting for 11.3% (n=6) of the reviewed articles. 33 , 34 , 37 , 41 , 42 , 46 Five reviewed articles (9.4%) studied E. coli 40 , 52 , 53 and Enterococcus spp. 30 , 54 56 Two different strains of E. coli were also studied, namely E. coli ST131 35 and O157:H7.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that these secondary rpoB mutations likely contributed to enhanced transmission and dispersal of KZN/LAM4 via enhanced resistance to rifampin and recovery of overall pathoadaptive fitness versus the L452P single mutant. L452P confers only low-level rifampin resistance, whereas mutations at position 435 (including D435Y and D435G) are associated with distinctly higher rifampin MICs (50), and in LAM4/KZN acquisition of D435G likely augmented rifampin resistance versus the L452P single mutant (51). Recent studies have implicated changes in protein stability (52) and transcriptional efficiency (53) as important determinants of how putative compensatory mutations impact fitness in rifampin-resistant Mtb .…”
Section: Discussionmentioning
confidence: 99%
“…In M. tuberculosis , a recent study demonstrated that the rpoB V534M mutation occurred in a clinical outbreak strain and functioned as a compensatory mutation to ameliorate the fitness cost introduced by the primary mutation S450L [ 27 ]. Furthermore, several genome sequencing-based studies demonstrated that many rifampicin-resistant M. tuberculosis clinical isolates carry double/multiple rpoB mutations, with nonsynonymous mutations outside the RRDR commonly co-occurring with RRDR mutations and being more likely to appear in strains without rpoA or rpoC mutations [ 2 , 8 , 28 ], which suggests that these mutations may have a compensatory function.…”
Section: Introductionmentioning
confidence: 99%